Genetic analyses of wheat and molecular marker-assisted breeding. Genetics map and QTL mapping / Volume 1, (2015) - Tian, Jichun; Deng, Zhiying; Zhang, Kunpu; Yu, Haixia; Jiang, Xiaoling; Li, Chun
No abstract available